Malformations and mortality in the Asian common toad induced by exposure to Pleurolophocercous cercariae (Trematoda: Cryptogonimidae) - Jayawardena, U.A.; Tkach, V.V.; Navaratne, A.N.; Amerasinghe, Priyanie H.; Rajakaruna, R.S. (Elsevier, 2013)
Malformations and increased mortality due to infection by the digenetic trematode, Riberioa ondatrae have been reported for many species of amphibians. Severe malformations have also been reported in the Common Hourglass Tree Frog, Polypedates cruciger induced by Pleurolophocercous cercariae in Sri Lanka in addition to the changes in the behaviour, development and survival of the host. We exposed pre-limb bud stage tadpoles (Gosner stages 25-26) of the Asian Common Toad, Duttaphrynus melanostictus to the same pleurolophocercous type cercariae under laboratory conditions. Molecular and morphological identification showed that these cercariae belonged Acanthostomum burminis infecting freshwater snakes as definitive hosts. These cercariae induced malformations (27.8%) and reduced survival to metamorphosis (53.8%). The magnitude of the effects increased with the dose of cercariae. Types of malformations were mainly axial, such as scoliosis and kyphosis. Severe limb malformations such as extra or missing limbs as reported for amphibians exposed to R. ondatrae were not observed in the D. melanostictus. Same authors reported a higher percentage of malformations previously when P. cruciger was exposed to the cercariae A. burminis compared to D. melanostictus. However, tadpoles of D. melanostictus, which are smaller compared to those of P. cruciger, experienced higher mortality than P. cruciger tadpoles. Trematode induced malformations and mortality in amphibians are highly variable and depend on multiple factors such as host species differences such as resistance to infection and tolerance, life-history characteristics such as size at metamorphosis and length of the metamorphosis period, and other factors such as size of the amphibian at the time of trematode exposure.